2021
DOI: 10.1111/ajco.13574
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan attenuates human glioblastoma cells proliferation and oncogenicity by inducing the lipid oxidation

Abstract: Background Glioblastoma (GBM) is one of the most common primary brain tumors, which accounts up to 80% of malignant brain tumors and the 5‐year relative survival rate is below 5%. Recent studies showed that the lipid metabolism played an essential role in GBM development. As a peroxisome proliferators‐activated receptors γ (PPAR‐γ) agonist, telmisartan improves the lipid metabolism and has been used to treat hypertension for long time. It has also been shown to have anticancer function, such as in lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Singh et al, 2024 in his recent study have demonstrated potential anticancer effect of TS loaded nanocarrier in breast cancer [12]. Another work by Wang et al, 2021 showed effectiveness of TS delivered through solid-lipid nanoparticles again brain cancer [13]. The current research investigation, however, will differ significantly from all previously reported works of this type.…”
Section: Introductionmentioning
confidence: 76%
“…Singh et al, 2024 in his recent study have demonstrated potential anticancer effect of TS loaded nanocarrier in breast cancer [12]. Another work by Wang et al, 2021 showed effectiveness of TS delivered through solid-lipid nanoparticles again brain cancer [13]. The current research investigation, however, will differ significantly from all previously reported works of this type.…”
Section: Introductionmentioning
confidence: 76%
“…The studies indicated Telmisartan can be used to treat ESCA (Matsui et al, 2019), EAC (Fujihara et al, 2017), CHOL (Samukawa et al, 2017), and hematologic malignancies (Kozako et al, 2016). It has also been reported that Telmisartan can apply in the treatment of endometrial (Koyama et al, 2014), lung cancers (Rasheduzzaman et al, 2018), bladder and urological (Matsuyama et al, 2010), ovarian (Pu et al, 2016), colon (Lee et al, 2014), renal (de Araújo Júnior et al, 2015, prostate (Funao et al, 2008), gastric (Fujita et al, 2020), and breast (Kociecka et al, 2010) cancers, hepatocellular carcinoma (Oura et al, 2017), and GBM (Wang et al, 2021). Nilotinib can also be used to treat CHOL (Marin et al, 2018), DLBC (Robak and Robak, 2012;Cai et al, 2019), and THYM (Kelly, 2013;Simonelli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is upregulated in mesenchymal glioblastoma stem cells, with agonism suppressing growth [329]. D. Telmisartan in NSCLC: Several studies show longer survival in NSCLC in patients receiving an ARB [330][331][332][333]. This effect, although slight, has been consistently found across studies.…”
Section: Telmisartanmentioning
confidence: 97%